2022
DOI: 10.1371/journal.pone.0258283
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequences of epidermin and nukacin encoding plasmids from oral-derived Staphylococcus epidermidis and their antibacterial activity

Abstract: Staphylococcus epidermidis is a commensal bacterium in humans. To persist in the bacterial flora of the host, some bacteria produce antibacterial factors such as the antimicrobial peptides known as bacteriocins. In this study, we tried to isolate bacteriocin-producing S. epidermidis strains. Among 150 S. epidermidis isolates from the oral cavities of 287 volunteers, we detected two bacteriocin-producing strains, KSE56 and KSE650. Complete genome sequences of the two strains confirmed that they carried the epid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Genome sequencing was performed as previously described, with some modifications ( 29 , 30 ). Briefly, bacterial cells were grown in TSB for 16 h at 37°C and harvested at 13,000 × g for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Genome sequencing was performed as previously described, with some modifications ( 29 , 30 ). Briefly, bacterial cells were grown in TSB for 16 h at 37°C and harvested at 13,000 × g for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…All fresh media were kept under anaerobic conditions for at least 5 hours. Lactococcus lactis (ATCC11454 [25], QU5 [29]), Staphylococcus epidermidis (KSE56, KSE650 [30]), Streptococcus mutans (KSM2, KSM13, KSM157, KSM170 [31]) and Enterococcus mundtii QU2 [32], were grown aerobically in trypticase soy broth (TSB) at 37 ˚C with (Streptococcus, L. lactis and Enterococcus) or without (S. epidermidis) 5% CO 2 .…”
Section: Plos Onementioning
confidence: 99%
“…In another study, epidermin showed antibacterial activity against 81.3% of tested S. aureus involved in human infections, including MRSA endemic clones in Brazil ( Nascimento et al, 2006 ). Epidermin also exhibited antibacterial effects against S. haemolyticus , S. capitis , S. simulans , S. saprophyticus , S. hominis , and S. epidermidis , although no activity was observed against some tested S. aureus ( Nakazono et al, 2022 ).…”
Section: Bacterial Amps That Have Antibacterial Activity Against Stap...mentioning
confidence: 99%
“…Nukacin ISK-1 showed a bacteriostatic effect against Bacillus subtilis by stopping cell growth without pore formation ( Asaduzzaman et al, 2009 ) while exhibiting bactericidal activity against Micrococcus luteus and S. simulans via pore formation and cell lysis ( Roy et al, 2014 ). Several variants of nukacin have been reported, including nukacin KQU-131 produced by S. hominis ( Wilaipun et al, 2008 ), nukacin 3299 produced by S. simulans ( Ceotto et al, 2010 ), and nukacin IVK45 and nukacin KSE650 produced by S. epidermidis ( Janek et al, 2016 ; Nakazono et al, 2022 ). Nukacin ISK-1 exerted a bacteriostatic effect against MRSA planktonic cells; however, activity against biofilm cells was not observed ( Okuda et al, 2013 ).…”
Section: Bacterial Amps That Have Antibacterial Activity Against Stap...mentioning
confidence: 99%
See 1 more Smart Citation